Ai-Driven Innovation In Islamic Schools: Impacts, Opportunities And Ethical Challenges - Suryana, Agus; Mustaqim, Ismail; Rois, Ajun (Al-Abshar: Journal of Islamic Education Management, 2025)
The rapid advancement of Artificial Intelligence (AI) has transformed educational practices, including those within Islamic schooling systems. This study investigates the challenges, opportunities, and ethical implications of integrating AI technologies into Islamic education. The research aims to analyze how AI tools—such as adaptive learning systems, gamified instruction, digital learning content, and automated administration—enhance learning personalization, access, and engagement while maintaining Islamic educational values. Employing a qualitative descriptive approach, the study synthesizes findings from academic literature, case studies, and expert perspectives on AI-based pedagogy in Islamic contexts. The results reveal that AI contributes positively to improving instructional efficiency, contextualized learning, and global collaboration among Islamic institutions. However, the findings also highlight critical ethical concerns, including content conformity with Islamic teachings, data privacy, the risk of dehumanization in learning, and algorithmic bias. These issues underscore the need for value-sensitive AI design that complements, rather than replaces, human educators. The study contributes to the discourse on responsible technology integration in religious education, proposing a framework for ethical and culturally grounded AI implementation that preserves the spiritual, moral, and humanistic essence of Islamic learning.